1985
DOI: 10.5465/amr.1985.4278108
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Contingency Model of Strategic Risk Taking

Abstract: And -which is more -you'll be a Man, my son. Rudyard KiplingThe image of the corporate executive as a bold, risk-taking, wheeler-dealer has become part of the folklore of American business. Durant, Ling, Lear are names which conjure up pictures of strategists willing to make one heap of all their profits and risk it on one project, one idea, one foray into the stock market. Yet when Sloan (1965) In recent years, interest in the importance of risk taking in strategy has grown tremendously (Bettis, 1983).Strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
124
0
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 444 publications
(126 citation statements)
references
References 44 publications
1
124
0
1
Order By: Relevance
“…The differences in risk for firms in emerging economies can be readily observed in the level of emphasis placed in an emerging economy on pioneering new technologies. Baird and Thomas (1985) argue that committing resources to a new venture unrelated to existing ones is perceived to be risky, especially if it entails new markets or products. In emerging economies, private firms are generally viewed as risky because they are relatively new (Ahlstrom & Bruton, 2002).…”
Section: Caveatsmentioning
confidence: 99%
“…The differences in risk for firms in emerging economies can be readily observed in the level of emphasis placed in an emerging economy on pioneering new technologies. Baird and Thomas (1985) argue that committing resources to a new venture unrelated to existing ones is perceived to be risky, especially if it entails new markets or products. In emerging economies, private firms are generally viewed as risky because they are relatively new (Ahlstrom & Bruton, 2002).…”
Section: Caveatsmentioning
confidence: 99%
“…Also, shareholder approval may be hard to obtain because this approach does not fit shareholders' short-term time horizons [46]. Studies have shown that while costly and risky implementation of circular economy principles are not being implemented, managers are intrigued by perceptions of growth potential [54], and an increased need to manage market turbulence [55][56][57] through the adaptation of circular business models.…”
Section: Contingency and The Structural Influence Of The Circular Ecomentioning
confidence: 99%
“…Past research present the perceived risk as the customer accompanying all purchases to varying degrees and influencing buying behavior (Cox, 1964). Perceived risk may also be defined as an individual's level of control over uncertain conditions (Baird& Thomas, 1985).Perceived risk has multiple dimensions as well including social, financial, physical, psychological, time, and performance risks (Stone & Gronhaug, 1993). Therefore, it also has been identified as an influential factor in the earlier phases of the purchase process (Dowling & Staelin, 1994).Perceived risk has been widely discussed, and studies have shown that perceived risk is a critical factor influencing customer decisions and behaviors (Chen, Chen, Hsiao, and Chiu, 2016;Chen & Chang, 2012).…”
Section: Journal Of Management Researchmentioning
confidence: 99%